2004
DOI: 10.1097/00001756-200403010-00031
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic stimulation differentially modulates declarative and nondeclarative memory

Abstract: Declarative memory has been reported to rely on the medial temporal lobe system, whereas non-declarative memory depends on basal ganglia structures. We investigated the functional role of the subthalamic nucleus (STN), a structure closely connected with the basal ganglia for both types of memory. Via deep brain high frequency stimulation (DBS) we manipulated neural activity of the STN in humans. We found that DBS-STN differentially modulated memory performance: declarative memory was impaired, whereas non-decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 22 publications
5
36
1
Order By: Relevance
“…Considering the more specific effects of STN-DBS on WPT classification learning, one group found restitution of overall learning with StimON unlike StimOFF (Halbig et al 2004). A more recent study by Wilkinson and colleagues did not detect differences in the overall outcome on the WPT between PD patients with StimOFF or StimON (Wilkinson et al 2011) similar to our findings but found significantly better learning on low probability measures with StimON compared to StimOFF.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the more specific effects of STN-DBS on WPT classification learning, one group found restitution of overall learning with StimON unlike StimOFF (Halbig et al 2004). A more recent study by Wilkinson and colleagues did not detect differences in the overall outcome on the WPT between PD patients with StimOFF or StimON (Wilkinson et al 2011) similar to our findings but found significantly better learning on low probability measures with StimON compared to StimOFF.…”
Section: Discussionsupporting
confidence: 86%
“…Others have reported a decline in declarative memory performance after STN DBS (Faglioni et al, 1997;Halbig et al, 2004). For example, Alegret et al (2001) reported a postoperative decrease in verbal learning ability, using the Rey Auditory Verbal Learning Test, although no change was noted in the immediate condition.…”
Section: Memorymentioning
confidence: 97%
“…Thus, a review of the memory changes following STN DBS surgery is potentially confounded by the language effects noted above. Nevertheless, two studies reported memory improvements in PD patients following bilateral STN DBS (Halbig et al, 2004;Hilker et al, 2004). Halbig et al distinguished between declarative and non-declarative memory and found differential effects of DBS surgery (Halbig et al, 2004).…”
Section: Memorymentioning
confidence: 99%
See 2 more Smart Citations